Effect of Allium mongolicum Regel Powder Addition to the Diet and Aging Time on Physicochemical Properties and Antioxidant Capacity of Angus Beef - XIE Yaodi, GAO Huixia, HE Jianjian, SUN Chenxu, YU Aihuan, YAO Haibo, XU Lei, HU Jinsheng, WANG He, DUAN Yueyan, TANG Defu, LEI Zhaomin, LIU Wangjing (Shipin Kexue)
The purpose of this study was to investigate the effects of dietary addition of Allium mongolicum Regel powder (AMRP) and aging time on the physicochemical properties and antioxidant capacity of Angus beef. In this experiment, 24 healthy Angus cattle at (14 ± 2) months of age with similar body mass of (271.17 ± 17.6) kg were randomly divided into a control group and three experiment groups. The control group was fed a basal diet, and the experimental groups, LAMR, MAMR and HAMR, were fed a basal diet supplemented daily with 10, 15 and 20 g of AMRP per animal, respectively. The experimental period lasted for 135 days. The results showed that adding AMRP at different gradients to the diet improved the color of beef. With increasing aging time, the shear force first decreased and then leveled off on the third day (P > 0.05). Adding AMRP to the diet had no significant effect on the texture characteristics (P > 0.05). With increasing aging time, the springiness first increased (days 1 to 5) (P 0.05), and finally decreased significantly (days 7 to 9) (P < 0.05). Adding 15 g/d of AMRP to the diet increased intramuscular fat deposition, and with the increase in aging time, the content of intramuscular fat gradually increased (P < 0.05). Adding 10 g/d of AMRP to the diet improved the activity of total superoxide dismutase (T-SOD). In contrast, adding 20 g/d of AMRP to the diet improved the content of total antioxidant capacity (T-AOC) and reduced the content of malondialdehyde (MDA). AMRP improved the antioxidant capacity of beef with aging time, especially on the 5th day. Compared with the control group, the acid value of the LAMR group significantly increased (P < 0.01). During the whole aging period, the acid value first decreased and then tended to be stable, and the peroxidase activity decreased significantly (P < 0.01).